ダイ18ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1977 - 藤沢, 格; フジサワ, イタル; 山川, 康男; ヤマカワ, ヤスオ; 阿部, 豊雄; アベ, トヨオ; 福沢, 志津夫; フクサワ, シズオ; FUJISAWA, Itaru; YAMAKAWA, Yasuo; ABE, Toyoo; FUKUSAWA, Shizuo (1980)
P(論文) この報告は第18次南極地域観測隊の定常気象部門が,1977年2月1日から1978年1月31日まで,昭和基地において行った地上気象観測,高層気象観測,オゾン全量観測およびオゾンゾンデによるオゾン垂直分布の観測等の概要である.観測項目,観測方法,測器等は前年と同じであり,地上および高層気象観測の結果は,観測終了後ただちにWMOで規程された型式の電報で,モーソン基地経由でメルボルンの解析センターに通報した. This paper describes the results of routine observations of surface and aerological weather, total ozone measurement using Dobson's spectrophotometer and vertical distribution of ozone using special ozone radio sondes at Syowa Station (index number 89532) between 1 February 1977 and 31 January 1978. The main items of observation, method and equipments are the same as the previous year. The data of the surface and aerological observations were regularly reported to the World Meteorological Center in Melbourne via Mawson Station according to the WMO regulations. departmental bulletin paper